Hubungan Tingkat Pengetahuan, Sikap Dan Tingkat Pendapatan Dengan Perilaku Buang Air Besar Keluarga Di Desa Kerjokidul Kecamatan Ngadirojo Kabupaten Wonogiri - Nurfita Sari, Alviana; , Dr.Suwaji, M.kes (2016)
The habit of open defecation made contamination of drink water sources and pollution of water sources that can cause a variety of diseases. Purpose of this study to know the relationship of knowledge, attitude and income level with open defecation of family. This research method used descriptif correlation with cross sectional study design. The study population are head of family at Kerjokidul Village Ngadirojo Wonogiri as many as 1,220 people. A sample of 90 people with proportional stratified random sampling technique. The statistical test used chi square test by SPSS 17. Results showed that there is relationship between level of knowledge with open defecation of family (p = 0.001). There is no relationship between attitude with open defecation of familiy (p = 0.079). There is a relationship between income level with open defecation of family (p = 0.007). Keyword : knowledge, attitude, income level, open defecation